Challenges in diagnosing cryptococcosis among HIV-infected patients in southern Mozambique and opportunities for intervention in contexts of limited resources: A pre-implementation study - José C. Langa; Troy D. Moon; Jahit Sacarlal; Mohsin Sidat (PLoS ONE, 2026)
Introduction Worldwide, cryptococcosis has increased due to HIV/AIDS, particularly in sub-Saharan Africa (SSA), where the mortality is high. Laboratory diagnosis for cryptococcosis among HIV-infected patients remains a challenge in most SSA countries. This study aimed to explore facilitators, barriers to re-implementing the India ink test, and logistical factors that could support the successful rollout of this alternative diagnostic method in southern Mozambique. Methods We conducted a cross-sectional study using mixed methods approaches in six hospitals across southern Mozambique over three months. Clinicians and laboratory technicians were asked to complete a questionnaire aimed to capture sociodemographic data, as well as current practices and clinical approaches with respect to cryptococcal diagnosis and clinical management. Subsequently, individual in-depth interviews were conducted to understand current challenges in the diagnosis of cryptococcosis and to assess facilitators, barriers, and potential opportunities for interventions. Quantitative data were captured through REDCap and subsequently analyzed using SPSS statistical program, while qualitative data were analyzed manually using a combination of content and thematic analysis approaches. Results A total of 98 healthcare providers (67 clinicians and 31 laboratory technicians) participated in the study. The mean age of the participants was 35 years. More than half were female (58.2%) and had at least five years of relevant work experience (53.1%). Challenges in diagnosing and managing cryptococcal disease were mainly related to 1) frequent shortages in the stocks of cryptococcal rapid antigen test, 2) contextual challenges in collecting cerebrospinal fluid samples, and 3) frequent shortages in the stocks of antifungal medications. In contrast, all study facilities had availability of microscopes, recognized the need for cryptococcal screening services, and had clinicians and laboratory technicians willing to collaborate for eventual roll-out of the test as routine practice. Conclusion Frequent stock-outs of rapid diagnostic tests and challenges associated with performing lumbar punctures are barriers to routine screening for cryptococcosis. In contrast, we have identified the universal availability of microscopes and health workers’ recognition of the problem, as well as their willingness to collaborate, as potential facilitators to leverage for the successful reintroduction of India ink microscopy of urine samples as a low-cost laboratory test alternative.